An Exploration - Developing an Online Travel Business - Gan, Hsia Yen, Gerald (2009)
The global travel market is a major industry contributing 9.4% (USD 5,474bn in 2009) to the world’s GDP and employs over 225 million people. Over the last four years the Travel & Tourism industry showed four consecutive years of growth with an average of 3.6% p/a, however growth has slowed down since the second half of 2008, due to the economic climate.